Rules of origin in EU-ACP economic partnership agreements - Eckart Naumann (International Centre for Trade and Sustainable Development (ICTSD), 2009)
The paper provides an analysis of different rules of origin that currently apply between the EU and the ACP countries in sectors like textile and clothing, and fisheries. With the end of the Cotonou agreement and its replacement by the still incomplete EPAs, the rules of origin provisions applicable to exports from different ACP countries became ever more complex, but also less restrictive in some cases. For the ACP countries that were able to initial an Interim EPA, market access to the EU is provided for by an EU Council Regulation that guarantees the continuation of non-reciprocal preferences until the EPAs are implemented; this includes some specific rules of origin as well. For ACP countries that did not sign an Interim EPA, preferential market access to the EU falls within the provisions of the EU's Generalized System of Preferences (GSP) or the Everything but Arm's Initiative'(EAI), with their corresponding, different rules of origin ...
Keywords: 330